CHARACTER EXPRESSION IN LITERARY TRANSLATION - Yusupov, Oybek (Журнал иностранных языков и лингвистики, 2021)
To improve the education of each person, it is important to get acquainted with the masterpieces of world literature. However, not everyone can learn works in the original language. It is only thanks to the writers-translators that invaluable treasures of world literature become available to us. It is impossible to overestimate the translation of literature, since with its help different peoples exchange thoughts and ideas with each other. And when we read a translated text, we perceive it as fiction, and do not think about what kind of work the translator put in to convey the meaning of the original literary work as accurately as possible. Translation of literary texts is complicated by a high semantic load, and the translator often has to create a text in another language anew, and not reproduce it from another language. Much influences the perception of the text: culture, subtext, national characteristics, everyday life, etc., therefore it is important for the translator to correctly adapt the text to all these conditions.